2014
DOI: 10.5130/ajceb.v14i2.3778
|View full text |Cite
|
Sign up to set email alerts
|

Modifications to standard forms of contract: the impact on readability

Abstract: Lack of clarity in contract documents can lead to disputes between contracting parties. Standard form contracts have evolved due to construction business becoming increasingly complex and the difficulty in drafting bespoke conditions of contract for each project. Numerous advantages have been identified in using standard forms of contract. However, clients often modify some clauses in order to include specific requirements for a project. While the consequences of ill-modifications to standard forms have been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Therefore, standard contract forms have been frequently used in the construction industry to reduce clarity and readability problems [30]. However, while adopting standard contract forms, various modifications in some clauses are made by clients to satisfy requirements of the projects [22]. Rameezdeen and Rodrigo [22] found that modifications to standard contract forms generally make the contracts more difficult to read.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, standard contract forms have been frequently used in the construction industry to reduce clarity and readability problems [30]. However, while adopting standard contract forms, various modifications in some clauses are made by clients to satisfy requirements of the projects [22]. Rameezdeen and Rodrigo [22] found that modifications to standard contract forms generally make the contracts more difficult to read.…”
Section: Related Workmentioning
confidence: 99%
“…However, while adopting standard contract forms, various modifications in some clauses are made by clients to satisfy requirements of the projects [22]. Rameezdeen and Rodrigo [22] found that modifications to standard contract forms generally make the contracts more difficult to read. All these considerations require a thorough analysis of risk factors affecting readability of construction contracts for smooth contract administration.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…R. Rameezdee et al [25] found that most of the problems in construction projects were related to the contractual behavior of individual key participants in the project. The contractual behavior of the key participants i.e delay in paying interim payment, late in giving possession, architect's behavior, adversarial relationship, poor communication are among other things that affect the project performance [26], [27], [28] and [29].…”
Section: Introductionmentioning
confidence: 99%